COOPERATION OF THE UZBEKISTAN SSR WITH THE GDR IN THE FIELD OF SCIENCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This scientific article reflects the cooperation between Soviet Uzbekistan and the GDR in the field of science. In particular, it provides scientific information about mutual personnel exchanges, international youth festivals, and scientific meetings dedicated to the analysis of scientific achievements.